Comparison of MRI and CT in the Evaluation of Unilateral Maxillary Sinus Opacification. (9th July 2021) - Chua, Elise; Navaratnam, Annakan V.; St Leger, Dominic; Lam, Vincent; Unadkat, Samit; Weller, Alexander
Abstract : Objectives . To evaluate the diagnostic performance of MRI compared with CT in differentiating neoplastic from infectious/inflammatory causes of complete unilateral maxillary sinus opacification (UMSO). Although MRI is increasingly used, no studies validate its utility compared to CT or nasal endoscopy in this context. Methods . A retrospective analysis of 49 patients presenting with complete UMSO to a tertiary referral centre was performed, investigated with both CT and MRI. Two head and neck radiologists independently reviewed each imaging modality and recorded both a final diagnosis and Likert-scale diagnostic certainty score. A consensus radiological diagnosis was determined, stratified into potentially neoplastic or infectious/inflammatory aetiology, and compared with nasal endoscopy and final diagnosis. Diagnostic performance and interoperator agreement for predicting neoplasia were calculated. Results . Both CT and MRI demonstrated high sensitivity and negative predictive value for neoplasm, although MRI was more specific (79%; 95% CI: 60–92%) than CT (14%; 95% CI: 4–32%), with a higher positive predictive value. MRI was more accurate (88%; 95% CI: 75–95%) than CT (49%; 95% CI: 34–64%) in diagnosing neoplasia. MRI had significantly higher diagnostic certainty Likert scores than CT (p < 0.0001 for both observers). Interobserver agreement was fair for CT (kappa coefficient = 0.327) and excellent for MRI (kappa coefficient = 0.918). Conclusions . MRI is more specific than CT in characterising UMSO, with greater diagnostic certainty and reproducibility. The additive diagnostic value of MRI complements CT, potentially reducing diagnostic delays in some cases and the need for diagnostic endoscopic sinus surgery in others. We recommend MRI incorporation into the diagnostic pathway for patients with UMSO.